Thoracic Outlet Syndrome in Sport: A Systematic Review - Garraud, Thomas; Pomares, Germain; Daley, Pauline; Menu, Pierre; Dauty, Marc; Fouasson-Chailloux, Alban (Frontiers in Physiology, 2022)
Thoracic outlet syndrome (TOS) is a rare and heterogeneous syndrome secondary to a compression of the neurovascular bundle in the thoracic outlet area. Muscle hypertrophy is recognized to induce vascular or neurogenic compression, especially in sports involving upper-arm solicitation. Athletes represent a distinctive population because of a specific management due to an ambitious objective, which is the return to high-level competition. We evaluated the scientific literature available for the management of TOS in athletes. Article research extended to March 2021 without other restriction concerning the date of articles publication. The search was performed independently by 2 assessors. A first preselection based on the article titles was produced, regarding their availability in English or French and a second preselection was produced after reading the abstracts. In case of doubt, a third assessor’s advice was asked. Case reports were selected only if the sport involved was documented, as well as the level of practice. Cohorts were included if data about the number and the sport level of athletes were detailed. Seventy-eight articles were selected including 40 case reports, 10 clinical studies and 28 reviews of literature. Baseball pitchers seem to be highly at risk of developing a TOS. The surgical management appears particularly frequent in this specific population. The prognosis of TOS in athletes seems to be better than in the general population, possibly due to their better physical condition and their younger age. Some studies showed interesting and encouraging results concerning return to previous sport level. Literature shows a strong link between TOS and certain sports. Unfortunately, this syndrome still lacks rigorous diagnostic criteria and management guidelines for athletes.